Women food producers in Barbados:assessment and policies - Cummins, Dianne (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
The general objetive of the Project was to draw u the bases for orienting the policies and actions of participating governments, with a view to improving the living and working conditions of women food producers in the región and, consequently, food security and the efficiency of the agricultural sector.